Revertants of an S49 cell mutant that expresses altered cyclic AMP-dependent protein kinase. - van Daalen Wetters, T (1982)
Dibutyryl adenosine 3',5'-phosphate (Bt2cAMP)-sensitive (Bt2cAMPS) revertants were isolated from a resistant S49 cell mutant carrying a structural gene lesion in the regulatory subunit of cAMP-dependent protein kinase (cA-PK). This was accomplished with a counter-selection in which, first, Bt2cAMP was used to reversibly arrest revertants, and then a sequence of treatments with bromodeoxyuridine, 33258 Hoechst dye, and white light was used to kill cycling mutant cells. Reversion rates in nonmutagenized cultures could not be accurately measured, but spontaneous revertants do occur and with frequencies of less than 10(-7) to 10(-5). The mutagens ethyl methane sulfonate (EMS), N-methyl-N'-nitro-N-nitro-soguanidine (MNNG), and ICR191 increased the reversion frequency. In all cases, reversion to Bt2cAMP sensitivity was associated with restoration of wild-type levels and apparent activation constant for cAMP of cA-PK. MNNG induced revertants whose cell extracts contained cA-PK activity distinguishable from that of wild type by thermal liability. EMS did not. The counter-selection effectively isolates rare phenotypes and is therefore a useful tool in further somatic genetic experiments. The association of reversion with alterations in cA-PK function supports all previous data from this and other laboratories implicating cA-PK as the intracellular mediator of cAMP effects. Reversion is probably the result of a mutational event. Induction of reversion by ICR191 suggests the existence of a novel mechanism for generating revertants in somatic cells.